Candlelight for Rebecca - Greene, Jacqueline Dembar; Hunt, Robert 1952-; McAliley, Susan (Middleton, WI American Girl Pub., 2009)
While Rebecca Rubin helps her building's ailing superintendent take care of his homing pigeons, she puzzles over what to do with the Christmas centerpiece her teacher insisted she make but which has no place in her Jewish home.
Ahead of title: 1914.
770L
95557
Keywords: Jews -- New York (State) -- New York; Jews -- United States; Toleration; Christmas; Hanukkah; Schools; Homing pigeons; Pigeons; New York (N.Y.) -- History -- 20th century